(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACT This study aims to determine the implementation of the Smart Indonesia Program In SMP Negeri 2 Maiwa, Enrekang Regency by using a qualitative research type descriptive method. Informants consist of 13 people. Research data obtained through observation, interviews and documentation. Validation of the data by triangulation of sources, techniques and time then analyzed through data reduction techniques, data presentation and drawing conclusions. The results of the study indicate that the implementation indicators in this study are supported by four interrelated aspects, namely : 1) communication between implementers in encouraging the success of PIP policies has gone well but is still not effective, 2) resources, human resources and non-human resources are good, 3) disposition has been going well seen from how the implementing party provides services and information optimally, 4) the bureaucratic structure has not been fully functioning properly, which involves more than one bureaucratic structure, each party having different operational standards. Keywords : Policy Implementation, Smart Indonesia Program